(untitled) (Research, Society and Development, 2020)
This article approaches some general aspects of information and communication technologies (ICT) in foreign language teaching, more specifically its use as a strategy of the teaching-learning process in the teaching of English and Spanish, in two campuses of a Federal School system in the state of Ceará, Brazil, before the Covid-19 Pandemic and the introduction of remote education in that institution. The analysis included the use of ICT considered by teachers as an important contribution to the process of teaching-learning foreign languages, as well as the technological tools identified used in teaching practice. The study also exposes barriers to greater use of these resources in educational practices. Although the teachers point out it as a relevant inclusion of ICTs in their teaching practice for more meaningful learning, such use is below the daily technological evolution in which immerses everyone. Most teachers say they don’t use new technologies with much frequency in their classrooms. They prove its little use with the following factors: precariousness of the institution’s physical infrastructure, which does not have good access to the Internet; socioeconomic problems, as some students do not have Internet in their homes; lack of teacher training, which makes it impossible to explore a greater diversity of these resources; the teacher’s workload, who is not often not motivated neither with time to carry out ICTs.